2017
DOI: 10.24251/hicss.2017.048
|View full text |Cite
|
Sign up to set email alerts
|

Social Collaboration Analytics for Enterprise Collaboration Systems: Providing Business Intelligence on Collaboration Activities

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…To achieve this, we designed an examination tool (shown in Table 2), that uses concepts from SocDOnt [29] and is guided by the first three dimensions of the Social Collaboration Analytics Framework (SCA) [23]. For each module in UniConnect, we identified the space (SCA: where) and the container (SCA: content type) in which a user can create items (SCA: content components).…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve this, we designed an examination tool (shown in Table 2), that uses concepts from SocDOnt [29] and is guided by the first three dimensions of the Social Collaboration Analytics Framework (SCA) [23]. For each module in UniConnect, we identified the space (SCA: where) and the container (SCA: content type) in which a user can create items (SCA: content components).…”
Section: Researchmentioning
confidence: 99%
“…We analyzed the database schema of UniConnect and identified the relevant databases, tables, fields and their relationships. Guided by the classification of data sources for Social Collaboration Analytics from [23], we looked at transactional data (1 database), usergenerated content data (6 databases) and organizational data (2 databases). Our analysis of the content data identified that there is exactly one database for each type of container storing social documents.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterprise collaboration platforms are complex, large-scale information infrastructures comprising an ecosystem of highly integrated tools and functionality to support collaborative work and information sharing in organizations [23,38]. In addition to their largescale, integrated nature, the key difference between these platforms and previous collaboration systems is the native integration of enterprise social software (ESS) such as wikis, blogs, social profiles, activities, likes, tags etc.…”
Section: Introductionmentioning
confidence: 99%